2018
DOI: 10.1002/csr.1644
|View full text |Cite
|
Sign up to set email alerts
|

The role of sustainable development and innovation on firm performance

Abstract: In the new economic scenario, characterized by a rapidly changing environment, companies are pushed into seeking new responses in order to survive and succeed. Companies are looking for new activities to improve their economic performance. Furthermore, these activities have been focused on innovation and/or socially responsible aspects. This paper analyzes the relationship between corporate social responsibility (CSR), innovation and its effect on performance. Especially, it shows if innovation has a fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 103 publications
6
97
1
Order By: Relevance
“…Although there are a considerable studies on CSR (e.g., Martínez‐Ferrero & Frías‐Aceituno, ) at the corporate and business levels, few works examine corporate responsibility at the functional level of the firm including supply chain strategy (Gallear, Ghobadian, & Chen, ); thus, we propose the notion of partner social responsibility as a safeguard mechanism to reduce the opportunistic behaviors when the supply chain partners invest in specific assets and transfer their knowledge to the other. Different with Guerrero‐Villegas, Sierra‐García, and Palacios‐Florencio (), who found that CSR acts as a mediator between innovation and objective performance, this study finds that partner social responsibility plays a moderating role not only in the link of specific investments and knowledge transfer but also in the knowledge transfer—green supply chain innovation performance link. Therefore, our research extends prior understanding to CSR.…”
Section: Discussioncontrasting
confidence: 96%
“…Although there are a considerable studies on CSR (e.g., Martínez‐Ferrero & Frías‐Aceituno, ) at the corporate and business levels, few works examine corporate responsibility at the functional level of the firm including supply chain strategy (Gallear, Ghobadian, & Chen, ); thus, we propose the notion of partner social responsibility as a safeguard mechanism to reduce the opportunistic behaviors when the supply chain partners invest in specific assets and transfer their knowledge to the other. Different with Guerrero‐Villegas, Sierra‐García, and Palacios‐Florencio (), who found that CSR acts as a mediator between innovation and objective performance, this study finds that partner social responsibility plays a moderating role not only in the link of specific investments and knowledge transfer but also in the knowledge transfer—green supply chain innovation performance link. Therefore, our research extends prior understanding to CSR.…”
Section: Discussioncontrasting
confidence: 96%
“…CSR items were adapted from a previously validated study (Guerrero-Villegas et al, 2018;Lindgreen et al, 2009;Martinez-Conesa et al, 2017), and comprised 22 items classified into 4 groups: customer, employee, community, and environment. The extent of involvement in CSR was measured using a 5-point scale (ranging from strongly disagree ¼ 1 to strongly agree ¼5).…”
Section: Variable Measurementmentioning
confidence: 99%
“…In this line and from the relationship marketing approach, CSR has been identified with three main dimensions, based on the theoretical model of the "triple bottom line" formulated by Elkington (2004) [11]: economic, environmental, and social sustainability, being the retail companies the ones that initially implemented this business. Although there is some previous work on sustainability from the point of view of the producer and of the supply chain (Hammer and Pivo, 2017 [12]; Bernal-Conesa et al (2017) [13]; or those including the CSR actions related to philanthropy (Arco-Castro et al, 2020 [14]; Guerrero-Villegas et al (2018) [15]), the protection of the environment, defending consumers, respect for workers' rights and helping the community [15]; Herrera et al, 2016 [16]; López-Pérez et al, 2018) [17], the sustainability model implemented by retailers has not yet been researched in depth.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%